2018
DOI: 10.5463/dcid.v28i4.666
|View full text |Cite
|
Sign up to set email alerts
|

The Family and Disability in Ghana: Highlighting Gaps in Achieving Social Inclusion

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 34 publications
4
39
0
4
Order By: Relevance
“…This is in line with Kassah (), who reported that low academic qualifications could account for high rates of unemployment or underemployment among individuals with a disability in Ghana. It is pertinent to reiterate that, in Ghana, negative cultural perceptions about the work capacity of persons with disabilities also mitigate against their efforts to find gainful employment (Opoku et al, ). The belief that persons with disabilities are cursed, and thus, their role in society is to survive on charity rather than seek employment, is widespread in Ghana (Agbenyega, ; Avoke, ; Baffoe, ).…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with Kassah (), who reported that low academic qualifications could account for high rates of unemployment or underemployment among individuals with a disability in Ghana. It is pertinent to reiterate that, in Ghana, negative cultural perceptions about the work capacity of persons with disabilities also mitigate against their efforts to find gainful employment (Opoku et al, ). The belief that persons with disabilities are cursed, and thus, their role in society is to survive on charity rather than seek employment, is widespread in Ghana (Agbenyega, ; Avoke, ; Baffoe, ).…”
Section: Discussionmentioning
confidence: 99%
“…In dominant Ghanaian culture, an individual's social support system is very important. However, in the lives of person with disabilities, social supports do not seem to be applicable due to stigmatization and dehumanization (Opoku et al, 2017). When there is no public or community support system, support of the individual with disability falls to the family.…”
Section: Abuse and Social Exclusion: Pwds And Caregiversmentioning
confidence: 99%
“…These efforts by the government present a new era of improving the social, economic and political well-being of people with disabilities. That notwithstanding, women with disability in Ghana continue to face substantial barriers in accessing social services including health [14][15][16][17], education [18,19] and economic activities [20][21][22][23]. More specifically, women with disability do not only face barriers in accessing SRH services and care but also difficulty in getting health information.…”
Section: Introductionmentioning
confidence: 99%